2018
DOI: 10.1037/fam0000405
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and aggression toward partners and children: Contextual influences of fear and anger.

Abstract: Trauma exposure is a consistent correlate of intimate partner aggression (IPA) and parent-to-child aggression (PCA) perpetration, and difficulties with emotions (particularly fear and anger) are hypothesized to underlie these relations. However, the absence of knowledge of the immediate, contextual influence of emotions on aggression renders existing conclusions tenuous. This study illustrates a new method for studying contextual influences on aggressive behavior. Quarterly for 1 year, 94 men and 109 women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The study offered a rare chance to analyze the findings in light of the continuing epidemic. Consistent with prior findings (Marshall et al, 2018 ), our results also showed that those exposed to COVID-19 tended to report more anxiety and aggression, furthermore to the anxiety’s complete mediation role on the connection between exposure to COVID-19 and aggression. However, on the basis of the differential susceptibility hypothesis (Valkenburg, P. M., & Peter, J., 2013 ), the risk of aggression is expected to vary based on the individual’s unique risk and protective factors.…”
Section: Discussionsupporting
confidence: 92%
“…The study offered a rare chance to analyze the findings in light of the continuing epidemic. Consistent with prior findings (Marshall et al, 2018 ), our results also showed that those exposed to COVID-19 tended to report more anxiety and aggression, furthermore to the anxiety’s complete mediation role on the connection between exposure to COVID-19 and aggression. However, on the basis of the differential susceptibility hypothesis (Valkenburg, P. M., & Peter, J., 2013 ), the risk of aggression is expected to vary based on the individual’s unique risk and protective factors.…”
Section: Discussionsupporting
confidence: 92%
“…Three incidents are then selected for review and probing of the context of aggression. The selection algorithm prioritizes incidents with the greatest number of aggressive behaviors and incidents in which spillover occurred while balancing incidents of IPA with incidents of PCA (see decision tree in Marshall, Roettger, Mattern, Feinberg, & Jones, 2018). Thus, for each interview, the number of IPA incidents probed can vary from zero (if no IPA was reported) to three (if three incidents of IPA, but no PCA, were reported).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to antecedents of IPV perpetration, trait‐level characteristics that are hypothesized to function as situational antecedents are well‐established (Capaldi et al, 2012), and effectively serve to identify individuals who may be at risk for perpetration. For example, meta‐analyses suggest that two common trait level characteristics strongly associated with IPV perpetration are shame and anger (e.g., Lawrence & Taft, 2013; Norlander & Eckhardt, 2005), and there is some evidence that anger may be a salient emotional state immediately before incidents of aggression (Marshall et al, 2018). However, less research exists in regard to the internal consequences of IPV perpetration, which could inform a complete functional analysis of the behavior and reduce the risk for further perpetration.…”
Section: Introductionmentioning
confidence: 99%